Implementasi Metode BCM (Bermain, Cerita, dan Menyanyi) terhadap Motivasi Santri dalam Proses Belajar di TPQ Al-Fattah Desa Wironanggan - Angga Dwi Prasetyo; Wiwin Mariyana (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Education is a process to change attitudes and behavior to make humans kill through teaching and exercise, processes, and how to educate. Education is not only an activity organized at school, but education is also held outside schools such as education in the Qur’an education park. Along with the development of times in the world, there are many new problems and never thought about before. Moreover, regarding the problems of education of the Qur’an which is still minimal and often ruled out. One of them is motivation in learning to recite the Qur’an, a lack of strategy in the learning method that can affect the encouragement of students to learn so that making learning less effective and learning goals are not fully achieved. With the administration of the BCM (Play, Stories, Singing) which is in accordance with the conditions of students who are still children will be able to increase the motivation of students to study. This service aims to increase understanding of how to increase the motivation to learn of students through the BCM (Play, Stories, Singing) method in TPQ. The method used is PAR (Participatory Action Research) which is to jump and be involved directly in implementing TPQ activities. After being carried out with the BCM (Play, Stories, Singing) there is a change in the increasing motivation of students in studying recite the Qur’an.